1992
DOI: 10.1111/j.1469-8137.1992.tb01062.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulated nitrogen rich and acid rain on the nitrogen‐fixing lichen Peltigera aphthosa (L.) Willd.

Abstract: summary The nitrogen‐fixing lichen Pettigera aphthosa (L.) Willd. was treated under semi‐natural conditions with simulated rain containing different combinations of ammonium, nitrate and sulphuric acid. Nitrogen in neutral solution had no negative effect on the nitrogen fixation rate. Sulphuric acid had a negative effect on nitrogen fixation rate, especially in combination with ammonium. The results could suggest an explanation for the sudden decline of P. aphthosa in southern Sweden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…The decrease of F v /F m ratios, A 435nm /A 415nm ratios and NDVI values in the lichen R. lacera exposed to anthropogenic activity in the study area, is in accordance with studies on the impact of acid rain on lichens ( Hallingbäck and Kellner 1992; Kytöviita and Crittenden 1994; Shevtsova and Neuvonen 1997). The occurrence of acid rain in the study area was already acknowledged.…”
Section: Discussionsupporting
confidence: 90%
“…The decrease of F v /F m ratios, A 435nm /A 415nm ratios and NDVI values in the lichen R. lacera exposed to anthropogenic activity in the study area, is in accordance with studies on the impact of acid rain on lichens ( Hallingbäck and Kellner 1992; Kytöviita and Crittenden 1994; Shevtsova and Neuvonen 1997). The occurrence of acid rain in the study area was already acknowledged.…”
Section: Discussionsupporting
confidence: 90%
“…The lower S deposition with stemflow explains why significant correlations of S concentration in stemflow were only found with cover of Cladonia coniocraea, Micarea prasina, and Parmelia saxatilis, whereas in the Harz Mountains, Hauck and Runge (2002) and Hesse (2002) concluded from strong correlations with the most frequent lichen species that inorganic S significantly affected the small-scale distribution of epiphytic li-chens on Picea abies. Experiments showed that SO 4 2-applied in acidic solution in concentration ranges such as found in the stemflow from the Harz Mountains is capable of causing damage to lichen thalli (Hallingbäck and Kellner 1992;Piervittori et al 1997). Lechowicz (1982) incubated Cladina stellaris for 15 min with simulated acid rain containing 100 µM SO 4 2-at pH 4 and found a reduced photosynthetic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…. short-term experiments cvanobacteria in lichen fixation after exposure to pH 3 4 (Gunther, 1988) or pH 3-0 (Hallingback & Kellner, 1992). In other studies a decline in nitrogenase activity has been observed at pH 4'0 (Englund, 1978;Fritz-Sheridan, 1985).…”
Section: Introductionmentioning
confidence: 95%